Reformulasi Digital Awareness melalui Kegiatan Menulis dan Berkomunikasi Efektif dalam Bahasa Indonesia di Media Sosial - Imma Rachayu; Yenni Fitria; Iqamah Syari; Ilham Ardiya Putra (Jurnal Dehasen Mengabdi, 2026)
The rapid development of information technology requires adolescents, especially vocational high school students, to have a high level of digital awareness. However, in reality, there is still widespread use of impolite Indonesian, the spread of false information, and a lack of communication ethics on social media. This Community Service Program (PKM) aims to reformulate students' digital awareness through training in creative writing and effective communication. The methods applied include outreach, workshops and practice, as well as evaluations in content writing, and simulations in writing content in cyberspace. The resulted of the activity indicated that students could optimally transform their digital awareness, overcoming the wall of pseudo-anonymity by teaching them that every digital interaction had really legal and social consequences. This transformation of students' digital awareness can be achieved through a multidisciplinary synergy between Educational Technology and Applied Linguistics.